2020
DOI: 10.1155/2020/1931737
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Insecure Attachment to Depression: Mediating Role of Sleep and Cognitive Reappraisal

Abstract: Previously, we have shown that neuromodulators are important factors in stress-induced emotional disorders, such as depression, for example, serotonin is the major substance for depression. Many psychological studies have proved that depression is due to insecure attachment. In addition, sleep is a major symptom of depression. Furthermore, serotonin is the substrate for both sleep and depression. To explore the role of sleep in the relationships between insecure attachment and depression, we investigated 755 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Regarding the literature described, our findings are consistent with, and extend, those reported by Liu et al (2020) and Warnke et al (2017). Like them, we found that emotion regulation was indirectly (via poor sleep quality) related to the presence of more depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Regarding the literature described, our findings are consistent with, and extend, those reported by Liu et al (2020) and Warnke et al (2017). Like them, we found that emotion regulation was indirectly (via poor sleep quality) related to the presence of more depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…However, to our knowledge, only two previous studies have investigated whether associations between emotion dysregulation and clinical symptoms are mediated by sleep disruption. 1 Liu et al (2020; N = 755 university students) found that less frequent use of cognitive reappraisal strategies was indirectly (via poor sleep quality) related to presence of depressive symptoms. Warnke et al (2017; N = 300 community-dwelling volunteers) found that the association between experiential avoidance and depressive symptoms was mediated by sleep quality.…”
mentioning
confidence: 99%
“…The neural mechanisms of the affective disorders (such as depression, anxiety, and functional neurological disorders) are yet to be uncovered [ 2 , 3 ]. The best way to study the affective disorders is through the basic emotional theory, which suggested that basic emotions are due to monoamines and peptides [ 4 , 5 ]. A widespread assumption in emotional theories is that human emotions are developed from a limited number of basic emotions, which are called basic , primary , or fundamental emotions [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, mindfulness can also help cognitive reappraisal, because an individual can treat the worries easily when they are relaxed with deep breathing. Previously, we have hypothesized that the human being has three primary kinds of core affects: reward, punishment, and stress [ 50 ], and they exclude from each other [ 50 ]. The individuals can have a good mood by focusing on positive emotions (reward) to transfer attention from stressful thoughts.…”
Section: Discussionmentioning
confidence: 99%